Marital Rape: An Evaluation of the Patriarchal Injustice in the Criminal Law (Amendment) Act, 2013 - Shivika, Choudhary (Christ University Law Journal, 2021)
The traditional belief that marriage provides a husband with sole rights over his wife, thereby exempting him from any prosecution for raping his wife, has been the justification for denying a woman the right to consent to sexual intercourse in marriage. Unfortunately, this belief has been a source of subjugation and exploitation of women at the behest of their husbands. Despite recommendations to revoke it, the Criminal Law (Amendment) Act, 2013 has retained the marital exception. The purpose of this article is to examine this dichotomy in the Criminal Law (Amendment) Act, 2013 that punishes rape as such, but does not penalise a husband raping his wife of fifteen years or above. Employing doctrinal method of research, this article analyses the various discrepancies and ambiguities in the Act of 2013 that perpetuate this culture of oppression and violence. Consent is the antithesis to rape. Thus, having examined the need for a married woman’s right to consent, this note examines the ensuing lacunae that grant legal sanction to child marriages, create an unexplained discrepancy in the punishment for rape, and create variations in the age of consent and the age for availing exception. The recognition of marital rape when spouses live separately and not otherwise appears to be a mysterious distinction. Further, treatment of marital rape